2016
DOI: 10.1108/rpj-02-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

3D printing with moondust

Abstract: Purpose -The purpose of this paper is to investigate the effect of the main process parameters of Laser Melting (LM) type Additive Manufacturing (AM) on multi layered structures manufactured from JSC-1A Lunar regolith (Moondust) simulant powder.Design/methodology/approach -Laser diffraction technology was used to analyse and confirm the simulant powder material particle sizes and distribution. Geometrical shapes were then manufactured on a Realizer SLM™ 100 using the simulant powder. The laserprocessed samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Both materials exhibited a reduction in the element concentration which is due to the low melting and decomposition temperatures of the mineral compounds, thus resulting in evaporation; this result is in line with previously gathered and published data by the authors (25).…”
Section: -Elemental Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Both materials exhibited a reduction in the element concentration which is due to the low melting and decomposition temperatures of the mineral compounds, thus resulting in evaporation; this result is in line with previously gathered and published data by the authors (25).…”
Section: -Elemental Analysissupporting
confidence: 91%
“…A previous experimental study, mainly focused on building structures out of lunar regolith simulant, gave a process parameters window and a laser energy density range of 0.9 -1 J/mm 2 where samples with no macroscopic defects were built (25). This paper covers a (Table 2), revealed a range of energy densities between 2.5 -4 J/mm 2 where sufficient fusion was evident between the particulates of the material.…”
Section: -Results and Discussionmentioning
confidence: 86%
“…), that would function autonomously and utilise indigenous materials as feedstock [8][9][10][11]. Previous studies have demonstrated that the application of a Powder Bed Fusion 3D printing process can manufacture structures/components from multi component ceramics that closely simulate Lunar and Martian regolith [12,13]. The need to use simulants is due to the scarcity of actual ET materials on Earth; there is a very small, closely guarded quantity of Lunar material and no samples acquired from Mars [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to the concept of 3D printing using extra-terrestrial/astro-materials as feedstock, and their state-of-the art available simulants 14 16 , have covered fundamental 17 23 and their engineering characteristics 24 28 to the development of process parameters 11,13 for the relevant 3D…”
Section: Introductionmentioning
confidence: 99%